Os determinantes macroeconômicos do spread bancário para pessoas físicas e jurídicas no Brasil: uma análise do período pós plano real - Matulovic, Marcio Oliveira (2015)
This research aims to empirically analyze the macroeconomic factors that determined the bank spread levels charged to individuals and legal entities in Brazil in the Real Plan postadoption period through December 2012. In order to do it a vector autoregression model was used with representative variables of macroeconomic factors. The research also shares some characteristics of the banking industry in Brazil and the credit market particularities for individuals and legal entities. These results suggest that: (i) the discount interest rate of the Central Bank of Brazil was the main macroeconomic determinant factor of the bank spread to individuals and legal entities; (ii) While an impact on the inflation level had greater influence on the spread practiced for individuals, an impact on the volatility of the discount interest rate of the Central Bank of Brazil had positive influence on the spread used for legal entities.